N-(2,4-Difluorophenyl)-5-methyl-1,2-oxazole-4-carboxamide hemihydrate - Jian-Guang Yu (Acta Crystallographica Section E, 2012)
In the title compound, C11H8F2N2O2·0.5H2O, the dihedral angle between the benzene and isoxazole rings is 8.08 (3)°. In the crystal, the components are linked by O—H...N and N—H...O hydrogen bonds, in which the water molecule acts as both a donor and an acceptor, into a tape with an R44(16) graph-set motif along the a axis. The water molecule is located on a twofold rotation axis. The methyl H atoms were treated as disordered groups over two sites with a refined site-occupancy ratio of 0.48 (6):0.52 (6).